Development co-operation : efforts and policies of the members of the Development Assistance Committee - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1987)
This report examines the measures being taken to resolve the two dominant problems on the 1984 agenda of development co-operation which had to do with retarded economic growth in Sub-Saharan Africa and fragile transitions from adjustment to development throughout the developing world.
Includes bibliographical footnotes.
usc 16/05/2018
Loans
Keywords: Economic assistance; Technical assistance; Organisation for Economic Co-operation and Development. Development Assistance Committee; Developing countries